Planning and conducting inquiry based mathematics course for future primary school teachers. - Samková, Libuše; Novotná, Jarmila; Moraová, Hana (Univerzita Karlova, Pedagogická fakulta, 2017)
The contribution presents some methodological issues related to a teaching experiment conducted under an educational research aiming at implementation of inquiry based mathematics education into university courses for future primary school teachers. The text introduces rudiments of inquiry based mathematics education, describes a one-year inquiry based teaching experiment which I prepared and conducted within a compulsory university course on arithmetic, and focuses on questions related to planning and performing such a course. The final part of the paper briefly mentions results of the education research associated with the experiment.
Jak připravit a vést badatelsky orientovaný kurz matematiky pro budoucí učitele 1. stupně ZŠ
Keywords: future primary school teachers; future teacher education; inquiry based mathematics education; teaching experiment; budoucí učitelé 1. stupně ZŠ; vzdělávání budoucích učitelů; badatelsky orientovaná výuka; výukový experiment